Eliminate x's
multiply 2nd equation by -2 ad add to first
2x+3y=9
<u>-2x-10y=-16 +</u>
0x-7y=-7
-7y=-7
divide by -7
y=1
sub back
2x+3y=9
2x+3(1)=9
2x+3=9
minus 3
2x=6
divide 2
x=3
x=3
y=1
(x,y)
(3,1)
D
Answer:
for six you got to get rid of the x's first the you it how u normally would
Step-by-step explanation:
Step-by-step explanation:
g = 28000 - 700t
because your started with 28000 gallons and every hour you have 700 less.
Answer:
im working on it
Step-by-step explanation:
Answer:
Step-by-step explanation:
Read simply, it is m + (r - 2). It is a very clear statement, so you can depend on the answer.